2023
DOI: 10.1007/s40292-023-00584-3
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Anxiety and Depression on Clinical Hypertension in Low-Income US Adults

Abstract: Introduction Depression and anxiety are common leading causes of disability and are associated with systemic effects including cardiovascular comorbidities. Low-income populations may experience higher frequencies of depressive or anxiety-related symptoms, and be at greater risk for developing hypertension. Aim We performed a cross-sectional study of low-income participants who completed hypertension and disability questionnaires as part of the 2017–2018 cycle of the Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
3
1
Order By: Relevance
“…Although some studies found associations between chronic diseases, for example, hypertension and diabetes mellitus, and risk of or worsening depression, 27 , 28 our data did not show any significant associations between presence of chronic diseases and worsening depression risk. Our relatively small sample size might be partly accountable for that.…”
Section: Discussioncontrasting
confidence: 99%
“…Although some studies found associations between chronic diseases, for example, hypertension and diabetes mellitus, and risk of or worsening depression, 27 , 28 our data did not show any significant associations between presence of chronic diseases and worsening depression risk. Our relatively small sample size might be partly accountable for that.…”
Section: Discussioncontrasting
confidence: 99%
“…[ 4 ] This reaffirms that anxiety and depression are common comorbidities among patients who have hypertension. [ 4 23 44 ] In addition, depression and anxiety were found among middle-aged adults and the elderly and this was consistent with the findings of a study in Afghanistan among adults with hypertension. [ 45 ] The study attributed this finding to the poor level of mental health services and facilities, in addition to the delay in accessing health care due to cost, especially in LMICs resulting in the challenge of diagnosing depression and anxiety at their onset among younger age.…”
Section: Discussionsupporting
confidence: 88%
“…In hypertensive patients, the relationship between hypertension and depression is quite unclear as some medications may also potentiate depression, while patients in a depressed state may also lose interest in taking medications and consequently have uncontrolled blood pressure. [ 21 ] Some large studies and studies conducted in the USA showed the presence of anxiety and/or depression among hypertensive patients,[ 22 23 ] and the presence of anxiety increased the odds ratio of hypertension. [ 24 25 ] Studies conducted in Nigeria, Ghana, and Ethiopia showed that a high proportion of the respondents who had hypertension also had symptoms of depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, respondents who reported occasional experiences of depressive feelings demonstrated an increased likelihood of hypertension, even if these occurrences were infrequent. Similarly, participants who reported experiencing daily or weekly anxiety were also more prone to having hypertension [56].…”
Section: Hypertension and Socioeconomic Statusmentioning
confidence: 97%